Azvudine efficacy in reducing mortality in COVID-19 patients - Zhong, Zhen; Liu, Xiao-feng; Zhou, Xiao-zhong; Zhong, Jia-ning; Zhou, Li-cheng; Li, Rong; Liu, Xian-fa (European journal of medical research, 2024)
Background Several therapeutic drugs have been authorized for the treatment of patients with Coronavirus disease 2019 (COVID-19). However, further research on the mechanisms of action, efficacy, and target populations of these novel therapeutic drugs are necessary. This study included mild, moderate, severe, and critical COVID-19 patients to evaluate azvudine’s effectiveness across different severity levels. Methods We conducted a retrospective cohort study of patients with COVID-19 admitted to our hospital from December 1, 2022, to March 31, 2023. Patients were divided into retrospective cohorts receiving azvudine antiviral therapy and standard treatment, and were followed-up for up to 28 days. Results Prior to data processing, azvudine treatment was associated with reduced mortality rates at 7 days (1.09/1000 persons vs. 5.06/1000 persons, P < 0.001) and 14 days (3.35/1000 persons vs. 5.65/1000 persons, P = 0.001). After propensity score matching, a decrease in mortality rates at 7 days (0.8/1000 persons vs. 6.29/1000 persons, P < 0.001), 14 days (3.42/1000 persons vs. 7.26/1000 persons, P < 0.001), and 28 days (4.33/1000 persons vs. 7.29/1000 persons, P = 0.003) were observed following azvudine treatment. After inverse probability of treatment weighting adjustment, the results were consistent with propensity score matching. In the clinical subgroup analysis, azvudine treatment intervention significantly reduced the 7-day (2.49/1000 persons vs. 14.59/1000 persons, P = 0.001 and 11.36/1000 persons vs. 66.99/1000 persons, P < 0.001), 14-day (5.22/1000 persons vs. 17.36/1000 persons, P < 0.001 and 17.08/1000 persons vs. 51.72/1000 persons, P = 0.002), and 28-day (7.58/1000 persons vs. 16.02/1000 persons, P = 0.014 and 20.43/1000 persons vs. 46.51/1000 persons, P = 0.008) mortality rates in hospitalized patients with severe and critical COVID-19. Conclusions The study suggests that in hospitalized patients with COVID-19, azvudine treatment significantly reduces patient mortality rates in hospitalized COVID-19 infections, wherein the effects are more pronounced in severe and critical patients.